2017
DOI: 10.1097/adm.0000000000000282
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Plaque Progression and Regression in Asymptomatic African American Chronic Cocaine Users With Obstructive Coronary Stenoses: A Preliminary Study

Abstract: Objective Although rapid progression of coronary atherosclerosis was observed in chronic cocaine users, it is unknown whether reduced cocaine use retards the progression of atherosclerosis. We investigated whether reduced cocaine use over a 12-month period was associated coronary plaque regression in cocaine users. Methods Fifteen African American chronic cocaine users with previously coronary CT angiography (CCTA) - confirmed >50% coronary stenosis in Baltimore, Maryland, were enrolled in a study to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Although existing studies have indicated the adverse impact of cocaine use on endothelial function, the molecular mechanisms that underlie the intervening effects of cocaine use on NNRTIs and their associated endothelial dysfunction need a further investigation. Our prior research has detected the association of cocaine use with endothelial damage measured as elevated ET‐1 concentrations and observed noncalcified plaque regression at 12‐month follow‐up in cocaine users who reduced their cocaine use . In human aortic endothelial cells, long‐term exposure to cocaine suppressed NO production and endothelial NO‐synthase expression .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although existing studies have indicated the adverse impact of cocaine use on endothelial function, the molecular mechanisms that underlie the intervening effects of cocaine use on NNRTIs and their associated endothelial dysfunction need a further investigation. Our prior research has detected the association of cocaine use with endothelial damage measured as elevated ET‐1 concentrations and observed noncalcified plaque regression at 12‐month follow‐up in cocaine users who reduced their cocaine use . In human aortic endothelial cells, long‐term exposure to cocaine suppressed NO production and endothelial NO‐synthase expression .…”
Section: Discussionmentioning
confidence: 95%
“…In human aortic endothelial cells, long‐term exposure to cocaine suppressed NO production and endothelial NO‐synthase expression . Cocaine use may also increase the concentrations of inflammation biomarkers, such as C‐reactive protein (CRP) and serum amyloid A . Systematic inflammation levels in HIV‐infected people may be reduced by ART regiments including NNRTIs but remain higher than those in HIV‐negative counterparts .…”
Section: Discussionmentioning
confidence: 99%
“…Recent data show high rates of premature heart disease and stroke deaths among Black males in New York City ages 18 to 65 with high rates in several neighborhoods in the Bronx (NYCDOHMH, 2017c). Given cocaine's association with myocardial injury and vascular events, including coronary plaque progression (Sandfort et al, 2017), it is not surprising to find high rates of cocaine involved overdoses in populations with high rates of underlying cardiovascular and cerebrovascular disease. However, this study cannot delineate the role of underlying cardiovascular diseases among the decedents of this study, especially in the setting of other substances present on toxicology.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these studies consistently suggest that (1) although ART substantially reduces HIV/AIDS-related mortality, long-term exposure to ART may be associated with comorbidities, including subclinical atherosclerosis, myocardial and hepatic steatosis, and telomere shortening, and (2) these ART-associated comorbidities could potentially be reduced or minimized in cocaine users with HIV infection if cocaine abstinence or even reduced use could be achieved. Although cocaine is highly addictive, we have demonstrated that cocaine abstinence or reduced use can be achieved with the use of a cash-based incentive intervention, and that cocaine abstinence or reduced use lowers a marker of endothelial dysfunction and is associated with coronary plaque regression (Lai, et al, 2015; Sandfort, et al, 2017). Despite the absence of FDA-approved medications for cocaine dependence, several candidate medications have demonstrated promising results in clinical trials (Kampman, 2009; Kampman, et al, 2015; Nuijten, et al, 2016).…”
Section: Discussionmentioning
confidence: 99%